Media in the Middle East - Abdelwahab El-Affendi (International Institute of Islamic Thought, 1996)
As evidenced by its subtitle, this book is a mighty ambitious work. The editors, recognizing the "woeful lack of information on the [Middle East's] media systems," present the book as "the first comprehensive study of the structure and functions of the mass media in the Middle East." And it took a lot of hard work, being the "culmination of more than two years of research and writing by 32 mass media scholars from across the Middle East and the United States." The books covers twenty-one countries. The Middle East is defined here as most Arab countries (Morocco, Sudan, Yemen, and Somalia were left out) plus Iran, Turkey, Israel, Pakistan, and Afghanistan. There is no question that a serious gap in information exists in the area the book attempts to cover. It is also safe to say that the researchers involved did a great job, assembling in one volume a wealth of infomiation on the structure of the media in the Middle East. One can at a glance glean up-to-date information about what publications are produced in each country, who owns them, what radio and television channels are available, what times they broadcast, what regulations exist, and how the media fit in the fuller picture ...